Racial re-inscriptions? Examining the potentials and limitations of self-identification variables in German survey research - Kim, Tae Jun (Frontiers in Sociology, 2025)
In recent years, quantitative methods have become a central tool in the fight against racism in Germany, offering empirical evidence to support anti-discrimination efforts. Among these methods, especially self-identification has gained prominence as a way to capture racialized experiences more accurately and to empower marginalized visibilities. By drawing on critical theories of racism, this paper argues that while self-identification may appear to challenge essentialist thinking, it can also risk re-inscribing race by stabilizing fluid identities into fixed categories. These risks are particularly salient in the German context, where official statistics have historically avoided racial categorization, and where recent shifts toward race-sensitive data collection raise new ethical and epistemological questions. By engaging with current methodological debates and highlighting both the contributions and limitations of quantitative approaches, this analysis calls for more reflexive, context-sensitive, and theoretically informed research designs.